ESG in Emerging Markets: The Value of Fundamental Research and Constructive Engagement in Looking beyond ESG Ratings. Issue 2 (9th September 2021) - Mobius, Mark; Ali, Usman
Abstract : The growth of ESG funds has been strong globally, but particularly within the emerging markets equity asset class. The founder and a partner of Mobius Capital Partners describe their differentiated approach to ESG investing in emerging markets using a series of case studies. Mobius Capital professes to be an emerging‐markets active ownership fund devoted to improving the ESG performance, while at the same time profiting from misleading ESG ratings and standards, in their portfolio companies. The authors discuss the pitfalls of using off‐the‐shelf ESG ratings and make a strong case for rigorous fundamental research combined with active ownership. Using a case study of Sunny Optical in China, the authors show that the mediocre external ESG rating of the company failed to reflect the company's ESG strengths. The authors also use the example of Yes Bank in India to demonstrate that a high ESG rating does not necessarily translate into high ESG standards. Third and last, the authors describe how a Taiwanese portfolio company's world‐class human capital and R&D capabilities were a core part of Mobius Capital's investment thesis.